Recaudación tributaria y su incidencia en las finanzas de la Municipalidad Provincial de Ucayali 2024 - Chauca Rengifo, Doris Isabel (2025)
The purpose of this final report was to determine the impact of tax collection on the finances of the Provincial Municipality of Ucayali 2024. It was a basic study, descriptive-correlational level with a non-experimental design. The population was 48 workers who were surveyed to collect information. The results showed that tax collection is regular (25%), this is because notifications to taxpayers are made through tax documents occasionally. However, a constant process of data purification and verification is maintained, ensuring consistency with physical evidence. In addition, coupons or booklets are regularly issued to inform taxpayers about their property tax debts. On the other hand, the finances of the Municipality are regular (25%), although there is efficient control over income from concessions and licenses, investment expenses are not always allocated to significant community projects. In addition, the lack of publication of detailed financial reports affects transparency and access to information by citizens. Finally, tax collection has a strong and significant positive influence on finance, explaining 61.5% of its variability.